Prevalence and genetic evolution analysis of porcine epidemic diarrhea virus and porcine circovirus type 2 in Sichuan Province, China, from 2023 to 2024 - Wu, Fang; Xu, Tong; Lai, Si-Yuan; Ai, Yan-Ru; Zhou, Yuan-Cheng; Ge, Liang-Peng; Sun, Jing; Liu, Zuo-Hua; Zeng, Xiu; Lang, Li-Qiao; Xu, Zhi-Wen; Zhu, Ling (Frontiers in Veterinary Science, 2024)
IntroductionPorcine circovirus type 2 (PCV2) and Porcine epidemic diarrhea virus (PEDV) are highly prevalent in Sichuan, significantly affecting the swine industry’s development. PCV2, known for its immunosuppressive effects, can compromise pigs’ immune systems, while PEDV typically causes diarrhea in piglets, leading to high mortality rates. Despite their impact, recent studies on the epidemiology and genetic diversity of PCV2 and PEDV within Sichuan Province remain limited.MethodsThis study examines clinical samples from 352 diarrheal piglets across 63 pig farms in 17 regions of Sichuan Province, revealing positivity rates of 42.33% (149/352) for PCV2 and 50.28% (177/352) for PEDV, with a co-infection rate of 27.56% (97/352). Notably, the highest positivity rates were observed in Ziyang for PCV2 at 61.90% (13/21), and in Meishan for PEDV at 73.81% (31/42), both regions also reported the highest co-infection rates of 47.62%.Results and discussionSeasonal analysis indicated that PEDV infections peaked during winter, whereas PCV2 showed no significant seasonal trends. Phylogenetic analysis identified 14 PCV2 strains, categorizing 2 as PCV2b (14.29%), 10 as PCV2d (71.43%), and 2 as PCV2e (14.29%). Among the 16 PEDV strains, 2 were classified as G1a (12.5%) and 14 as G2a (87.5%), with PCV2d and PEDV G2a identified as the predominant strains in the region. The study also highlights a high mutation rate at the antigenic sites of both viruses, potentially affecting vaccine efficacy. These findings underscore the need for ongoing surveillance and vaccine development tailored to the prevalent strains to improve control measures within the province.